Impact of Violence against Children in the Family Related To Law Number 23 Year 2004 Concerning Deletion of Violence in Household - Muhammad Rizal; Fathul Djannah (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2020)
The aim of the study is to find out the impact of violence against children in the family related. This research is a normative juridical study, the approach of which is a normative legal approach, which examines the rules of law relating to factors that cause violence against children in the household, the impact of violence on children in the household, efforts to protect children victims of violence in the home stairs. The result shows that the Factors that cause violence against children in the household are Psychodynamics models the occurrence of violence is caused by the lack of "mothering / traces of a mother." Someone who has never been cared for or cared for by a mother properly, then she cannot be a mother and care for her own children; Personality or character trait models, almost the same as psychodynamic, parents of children who are not mature enough, too aggressive, frustrated / bad character; Social learning model, lack of social skills, which is shown by feeling dissatisfied because of being a parent, feeling very disturbed by the presence of children, requires children to always behave like adults; Family structure model, which refers to the dynamics between families that have a causal relationship with violence; Environmental stress model, which sees children and women as a multidimensional problem and puts "life pressure" as the main cause.